2020
DOI: 10.2174/1381612826666200720235058
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Toll like Receptors in Cancer: Role of TLR Natural and Synthetic Modulators

Abstract: Background: Toll like receptors (TLRs) are a group of transmembrane receptors belonging to the broad class pattern recognition receptors (PRR), involved in the recognition of Pathogen Associated Molecular Patterns (PAMPs) and thereby inducing an immune response. Apart from these exogenous PAMPs, numerous endogenous PAMPs are also ligands for various TLRs thereby activating the TLR dependent immune response, subsequently leading to the onset of an inflammatory response. Prolonged activation of TLR by these end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 171 publications
0
6
0
Order By: Relevance
“…TLRs play crucial roles in antimicrobial immunity, autoimmunity, tumorigenesis, and tumor metastasis. [ 16,64,65 ] We found that RNF115 negatively regulated TLRs‐mediated autoimmunity and antimicrobial immunity. While accumulating evidence shows that RNF115 promotes cancer development and indicates RNF115 as a therapeutic target for cancer, [ 30,42 ] the identification of RNF115 as an inhibitor of the trafficking and the activation of TLRs raises the caution for autoimmunity when targeting RNF115 for cancer treatment.…”
Section: Discussionmentioning
confidence: 97%
“…TLRs play crucial roles in antimicrobial immunity, autoimmunity, tumorigenesis, and tumor metastasis. [ 16,64,65 ] We found that RNF115 negatively regulated TLRs‐mediated autoimmunity and antimicrobial immunity. While accumulating evidence shows that RNF115 promotes cancer development and indicates RNF115 as a therapeutic target for cancer, [ 30,42 ] the identification of RNF115 as an inhibitor of the trafficking and the activation of TLRs raises the caution for autoimmunity when targeting RNF115 for cancer treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Accumulating evidence has confirmed the pro-metastatic effect of the XCL1/XCR1 axis (36)(37)(38). Moreover, many studies have focused on applying small-molecule modulators targeting TLRs for cancer treatment (42,43). For example, the combination of immune modulatory oligonucleotide, an agonist of TLR9, and everolimus synergistically inhibited the growth and angiogenesis of RCC (44).…”
Section: Discussionmentioning
confidence: 99%
“…81 On the other hand, TLRs are a group of membrane receptors belonging to PRRs that are involved in identifying PAMPs, thereby causing an immune response. 82 The TLRs are the first line of defense against pathogens. 38 Therefore, targeting TLR and pathogenic factors of H. pylori to induce apoptosis and stimulate the immune system will be a promising, attractive, and helpful method for cancer prevention.…”
Section: Discussionmentioning
confidence: 99%